1991
DOI: 10.1002/hep.1840140117
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between insulin sensitivity, insulin secretion and glucose tolerance in cirrhosis

Abstract: Hepatic insulin extraction is difficult to measure in humans; as a result, the interrelationship between defective insulin secretion and insulin insensitivity in the pathogenesis of glucose intolerance in cirrhosis remains unclear. To reassess this we used recombinant human C-peptide to measure C-peptide clearance in cirrhotic patients and controls and thus derive C-peptide and insulin secretion rates after a 75-gm oral glucose load and during a 10 mmol/L hyperglycemic clamp. Cirrhotic patients were confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 50 publications
3
88
1
Order By: Relevance
“…However, their incremental C-peptide responses to glucose and tolbutamide were not significantly different. Our previous studies [3,26] and that of Tillil et al [27] suggested that first pass hepatic extraction of insulin falls at high rates of insulin secretion. Thus, the greater insulin response to tolbutamide compared to i.v.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…However, their incremental C-peptide responses to glucose and tolbutamide were not significantly different. Our previous studies [3,26] and that of Tillil et al [27] suggested that first pass hepatic extraction of insulin falls at high rates of insulin secretion. Thus, the greater insulin response to tolbutamide compared to i.v.…”
Section: Discussionmentioning
confidence: 85%
“…In both groups there was a strong relationship between these two estimates of insulin sensitivity (cirrhotic patients, r = 0.902,p < 0.001; control subjects r = 0.750,p < 0.02) Fasting insulin levels were increased five-fold in the non-diabetic cirrhotic patients and nine-fold in the diabetic cirrhotic patients. Interpretation of peripheral insulin levels in cirrhosis is complicated by their reduced hepatic insulin extraction [3,24]. C-peptide which is co-secreted with insulin in equimotar amounts but not extracted by the liver provides a much better index of insulin secretion [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations